Pengaruh Kemudahan Penggunaan Aplikasi dan Customer Experience terhadap Keputusan Pembelian di Marketplace Shopee pada Mahasiswa Fakultas Ekonomi Universitas Kristen Indonesia Toraja - Trivika Tambing; Althon K Pongtuluran; Chrismesi Pagiu (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The purpose of this research is to find out whether there is an effect of ease of use of the application and customer experience on purchasing decisions in the Shopee marketplace for students of the Faculty of Economics, Toraja Christian University of Indonesia. Data collection procedures from this study are: observation and questionnaires. The data analysis technique is quantitative with multiple linear regression tests. The results of calculations with the F test obtained the results of F count, 80.828 with F table 3.959. Based on the results of calculations with the T test on the ease of use variable, the results of T count (1.351) < T table (1.989) and on the customer experience variable, the results of T count (6.565) > T table (1.989). The conclusion of this study is that the ease of use variable does not affect purchasing decisions on the Shopee marketplace for students of the Toraja Christian University's economics faculty and the customer experience variable influences purchase decisions